The Invasion Curve: A Tool for Understanding Invasive Species Management in South Florida - Rebecca G. Harvey; Frank J. Mazzotti (EDIS)
South Florida has more than its share of invasive plants, reptiles, amphibians, fish, mammals, birds, and invertebrates. Nonnative species often spread quickly. Research and monitoring can help managers anticipate which species will cause harm before it is too late to remove them. Identifying where a species is on the invasion curve is the first step to taking management action. The invasion curve shows that eradication of an invasive species becomes less likely and control costs increase as an invasive species spreads over time. Prevention is the most cost-effective solution, followed by eradication. If a species is not detected and removed early, intense and long-term control efforts will be unavoidable. This 4-page fact sheet was written by Rebecca G. Harvey and Frank J. Mazzotti, and published by the UF Department of Wildlife Ecology and Conservation, November 2014.